2006
DOI: 10.1063/1.2402912
|View full text |Cite
|
Sign up to set email alerts
|

Magnetic-divertor stabilization of an axisymmetric plasma with anisotropic temperature

Abstract: Magnetohydrodynamic stabilization of an axisymmetric mirror plasma with a magnetic divertor is studied. An equation is found for the flute modes, which includes the stabilizing influence of ion temperature anisotropy and nonparaxial magnetic fields, as well as a finite ion Larmor radius. It is shown that if the density profile is sufficiently gentle, then the nonparaxial configuration can stabilize all modes as long as ion temperature is radially uniform. This can be demonstrated even when the density vanishes… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
12
0

Year Published

2010
2010
2013
2013

Publication Types

Select...
7

Relationship

3
4

Authors

Journals

citations
Cited by 9 publications
(12 citation statements)
references
References 15 publications
0
12
0
Order By: Relevance
“…The stability analysis of the divertor mirror, taking into account the effects of the ion finite Larmor radius, magnetic field line curvature, and the plasma compressibility, has been done. [19][20][21] It was reported that the flute modes were stabilized by the divertor mirror experimentally. [22][23][24] Because the classical radial transport is large around x-point, the diffusion forms locally stable pressure profile ͑with ‫ץ‬U / ‫ץ‬ ͒ in the neighborhood of magnetic null and unstable pressure profile outside this area and so ‫ץ‬pU ␥ / ‫ץ‬ =0 is not satisfied around the separatrix ͑i.e., around the plasma boundary͒, which can destabilize the flute modes.…”
Section: Flute Stabilitymentioning
confidence: 99%
See 1 more Smart Citation
“…The stability analysis of the divertor mirror, taking into account the effects of the ion finite Larmor radius, magnetic field line curvature, and the plasma compressibility, has been done. [19][20][21] It was reported that the flute modes were stabilized by the divertor mirror experimentally. [22][23][24] Because the classical radial transport is large around x-point, the diffusion forms locally stable pressure profile ͑with ‫ץ‬U / ‫ץ‬ ͒ in the neighborhood of magnetic null and unstable pressure profile outside this area and so ‫ץ‬pU ␥ / ‫ץ‬ =0 is not satisfied around the separatrix ͑i.e., around the plasma boundary͒, which can destabilize the flute modes.…”
Section: Flute Stabilitymentioning
confidence: 99%
“…21 Thus the self-consistent numerical simulation is necessary to estimate the flute instability in a divertor mirror.…”
Section: ‫ץ‬ ‫ץ‬ ͵ ͑Pmentioning
confidence: 99%
“…19 Historically the equilibrium calculation has been carried out in various divertor mirror cells for isotropic pressure plasma, 20 for anisotropic pressure plasma 19,21 and for kinetic KruskalOberman stability theory with anisotropic pressure. 22 The theoretical study of flute mode stability by a magnetic divertor was done first by Lane et al 23 The subsequently the theory was extended by Pastukhov and Sokolov 24 by taking into account the nonparaxial magnetic filed line curvature and then was extended further more by Sasagawa et al 25 by including the anisotropic ion temperature effects. The general concept of divertor stabilization in mirror-based plasma confinement systems were also discussed by Pastukhov.…”
Section: Introductionmentioning
confidence: 99%
“…2πψ gives the magnetic flux inside a surface of ψ = const, and ϕ corresponds to an angular coordinate. The remaining coordinate ζ is taken as the z-axis or along magnetic field lines [8,9]. The classical viscosity is included in Eqs.…”
Section: Basic Equationsmentioning
confidence: 99%